(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Music therapy is one of most popular methods used by psychologists and psychiatrists but anything new is well forgotten old. Music therapy can be extremely successful and helpful in many ways! Music therapy can help reduce the strife caused by stress, physical or mental pain, anxiety or panic attacks, anger, attitude and moods changes, and difficulty with sleeping. Being pregnant is a very beautiful and powerful experience for most women or at least, it ought to be so